Living together separately : Arabs and Jews in contemporary Jerusalem - Romann, Michael; Weingrod, Alex (Princeton University Press, 1991)
Focusing on the conduct of everyday life, rather than ideology. provides a look at the complex networks of practical relations developed by Jews and Arabs in over two decades of Israel control of the city (cont.).
"Written under the auspices of the Jerusalem Institute for Israel Studies."
Keywords: Palestinian Arabs -- Jerusalem.; Jews -- Jerusalem.; Arab-Israeli conflict -- 1973-1993.; Jerusalem -- Ethnic relations.; Palestiniens -- Jérusalem.; Juifs -- Jérusalem.; Relations judéo-arabes -- Histoire -- 1973-1993.; Jérusalem -- Relations interethniques.; Conflit israélo-arabe -- 1973-1993.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Arab-Israeli conflict; Ethnic relations; Jews; Palestinian Arabs; Middle East -- Jerusalem; Araber; Juden; Palästinenser; Jerusalem; Politischer Konflikt; Separatismus; Soziale Integration; Joden.; Palestijnen.; Etnische betrekkingen.; Relations Juifs-Arabes.; Jérusalem -- Politique et gouvernement.; Araber.; Juden.; 1973-1993; Arabs; Jerusalem (Israel)